Artificial intelligence for administrative simplification and public integrity - Lara Ortiz, María Lidón (2025)
This paper analyzes the impact that the application of artificial intelligence systems may have on the activities of public administrations from the perspective of Spanish law. Specifically, it considers the effects on the simplification of administrative procedures and the reduction of bureaucracy, as well as on the preservation of public integrity. Undoubtedly, all of this is aligned with the standards of good governance and raises new challenges for modern administrative law, which will need to be addressed in future regulations. This paper analyzes the current regulatory trends regarding administrative simplification and the preservation of administrative integrity, and raises the issue of the scope of incorporating artificial intelligence systems in these areas, highlighting the main problems that are expected from this.